Comparative Genomics of Herpesviridae Family to Look for Potential Signatures of Human Infecting Strains - Vikas Sharma; Fauzul Mobeen; Tulika Prakash (International Journal of Genomics)
Herpesviridae family is one of the significant viral families which comprises major pathogens of a wide range of hosts. This family includes at least eight species of viruses which are known to infect humans. This family has evolved 180–220 million years ago and the present study highlights that it is still evolving and more genes can be added to the repertoire of this family. In addition, its core-genome includes important viral proteins including glycoprotein B and helicase. Most of the infections caused by human herpesviruses have no definitive cure; thus, search for new therapeutic strategies is necessary. The present study finds core-genome of human herpesviruses that differs from that of Herpesviridae family and nonhuman herpes strains of this family and might be a putative target for vaccine development. The phylogenetic reconstruction based upon the protein sequences of core gene set of Herpesviridae family reveals the sharp splits of its different subfamilies and supports the hypothesis of coevolution of viruses with their hosts. In addition, data mining for cis-elements in the genomes of human herpesviruses results in the prediction of numerous regulatory elements which can be used for regulating the expression of viral based vectors implicated in gene therapies.